Peripheral Photopenia on Whole-Body PET/CT Imaging With 18F-FDG in Patients With Compartment Syndrome and Mesenteric Venous Thrombosis. (December 2020) - te Beek, Erik T.; Tangkau, Peter L.; van Esser, Stijn; Brouwer, Rolf E.; ten Broek, Marc R. J.
Abstract : Abstract: We present 2 cases that demonstrate photopenia in peripheral areas on whole-body PET/CT imaging with 18 F-FDG as a sign of absent perfusion with severe short-term complications. The scan of the first patient shows photopenia in the right ankle and foot, resulting from compartment syndrome, caused by hemolytic group A streptococcus bacteremia with endocarditis and septic emboli, necessitating lower leg amputation. The scan of the second patient shows photopenia in the transverse colon, resulting from mesenteric venous thrombosis caused by polycythemia vera, leading to necrosis and perforation of the transverse colon, necessitating transverse and right hemicolectomy.